2014
DOI: 10.1093/nar/gku276
|View full text |Cite
|
Sign up to set email alerts
|

Human single-stranded DNA binding protein 1 (hSSB1/NABP2) is required for the stability and repair of stalled replication forks

Abstract: Aberrant DNA replication is a primary cause of mutations that are associated with pathological disorders including cancer. During DNA metabolism, the primary causes of replication fork stalling include secondary DNA structures, highly transcribed regions and damaged DNA. The restart of stalled replication forks is critical for the timely progression of the cell cycle and ultimately for the maintenance of genomic stability. Our previous work has implicated the single-stranded DNA binding protein, hSSB1/NABP2, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 48 publications
1
51
0
Order By: Relevance
“…[3][4][5][6][7][8] Our generation and phenotypic analysis of cDKO mice has unmasked the compensatory and essential functions of Ssb1/Ssb2 in maintaining tissue homeostasis, which was unexpected from analysis of single knockout mouse models.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[3][4][5][6][7][8] Our generation and phenotypic analysis of cDKO mice has unmasked the compensatory and essential functions of Ssb1/Ssb2 in maintaining tissue homeostasis, which was unexpected from analysis of single knockout mouse models.…”
Section: Discussionmentioning
confidence: 99%
“…Depletion of SSB1 in cells results in increased radiosensitivity, defective repair of DNA double-strand breaks (DSBs), oxidative DNA damage, and failure to restart stalled replication forks. [3][4][5][6][7][8] Moreover, Ssb1 has been shown to regulate telomere homeostasis by protecting newly replicated G-overhangs of leading-and lagging-strand telomeres. 9,10 SSB1 is recurrently mutated in various cancers, and an SSB2/RARA fusion gene has been described in variant acute promyelocytic leukemia.…”
Section: Introductionmentioning
confidence: 99%
“…This uncoupling results in long stretches of ssDNA, leading to an ATR checkpoint response that helps to stabilize the fork and allows time to resolve the replication barrier by arresting cell cycle progression (Figure 4) (121). Stretches of ssDNA are protected by ssDNA-binding proteins such as RPA or human single-stranded DNA binding protein 1 (hSSB1) (130, 131). RPA binding to ssDNA inhibits annealing of short homologous sequences (as in short repeats) through microhomology-mediated repair and reduces secondary structures recognized by nucleases (132).…”
Section: Mrn and Replication Fork Dynamicsmentioning
confidence: 99%
“…Previous studies have suggested that both of these proteins function as mutually exclusive components of the sensor of single-stranded DNA (SOSS) complex in partnership with the integrator complex subunit 3 (INTS3) and hSSB-interacting protein 1 (hSSBIP1; SOSSC) [1619]. The depletion of any of these proteins has further been demonstrated to increase the sensitivity of cells to DNA damage caused by ionising radiation exposure and treatment with the topoisomerase I inhibitor, camptothecin [17, 20, 21]. Here, hSSB1 has been reported to stimulate resection of double-strand DNA break ends by the Mre11-Nbs1-Rad50 (MRN) [22, 23] and Exo1 [24] nucleases, as well as activation of the ATM kinase [20].…”
Section: Introductionmentioning
confidence: 99%